Preliminary studies on the biobleaching of loblolly pine Kraft pulp with Trametes trogii crude extracts - Da Re, Cristina Verónica (2008)
Trametes trogii (BAFC 463), Coriolus versicolor var. antarcticus (BAFC 266) and Trametes villosa (BAFC 2755) are Argentinean white-rot fungi that proved to be efficient ligninolytic enzyme producers in previous studies. The aim of the present work was investigating the ability of their crude extracellular extracts for the biobleaching of loblolly pine Kraft pulp. The production of laccase, manganese peroxidase, endoxylanase and endoglucanase was also evaluated. Out of the three fungi studied, the best biobleaching results were obtained with culture supernatants from T. trogii grown for 21 days in a synthetic medium with glucose and asparagine as carbon and nitrogen sources, respectively, with the addition of 1 mM copper sulfate. Such medium rendered high level of ligninolytic enzymes: 0.25 U ml-1 of manganese peroxidase and 44 U ml-1 of laccase. A strong brightness increase was attained after the enzymatic treatment followed by H2O2. Bleaching up to 82% ISO brightness (compared with 37% in the peroxide-bleached control) was obtained. Moreover, after the enzymatic treatment, hydrogen peroxide requirements decreased (as reflected by the higher residual peroxide), and the pulp luminance reached a value of 92.5. Addition of known laccase mediators such as HBT, ABTS, and HBA did not improve the process. The supernatant did not significantly lose its bleaching capacity even after successive recovery and reapplication to unbleached pulp. Correspondingly, laccase and manganese peroxidase activities in the recovered supernatant, exhibited near 100% of their initial values.